(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The article tries to analyze the transformations that Law n. 833 of 1978, which established the national health service, forty years after its promulgation. The equality, fairness and universality of the service have been questioned by economic crises, by the new regional structure of the Italian state, by the weaker application of the principle of equality. Despite everything, however, that system proves to be still functioning and health protection must remain universal, financed by general taxation and equal for all.